Voltage-driven superconducting weak link as a refrigerator for cooling of nanomechanical vibrations - Sonne, G.; Peña-Aza, M.E.; Shekhter, R. I.; Gorelik, L.Y.; Jonson, M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
We consider a new type of cooling mechanism for a suspended nanowire acting as a weak link between two superconductive electrodes. By applying a bias voltage over the system, we show that the system can be viewed as a refrigerator for the nanomechanical vibrations, where energy is continuously transferred from the vibrational degrees of freedom to the extended quasiparticle states in the leads through the periodic modulation of the inter-Andreev level separation. The necessary coupling between the electronic and mechanical degrees of freedom responsible for this energy-transfer can be achieved both with an external magnetic or electrical field, and is shown to lead to an effective cooling of the vibrating nanowire. Using realistic parameters for a suspended nanowire in the form of a metallic carbon nanotube we analyze the evolution of the density matrix and demonstrate the possibility to cool the system down to a stationary vibron population of 0.1. Furthermore, it is shown that the stationary occupancy of the vibrational modes of the nanowire can be directly probed from the dc current responsible for carrying away the absorbed energy from the vibrating nanowire.